Investigating intestinal permeability and gut microbiota roles in acute coronary syndrome patients. (August 2019) - Alhmoud, Tarik; Kumar, Anand; Lo, Chien-Chi; Al-Sadi, Rana; Clegg, Stacey; Alomari, Ihab; Zmeili, Tarek; Gleasne, Cheryl Diane; Mcmurry, Kim; Dichosa, Armand Earl Ko; Vuyisich, Momchilo; Chain, Patrick Sam Guy; et al.
Abstract: Background: Acute Coronary Syndrome (ACS) is a leading cause of morbidity and mortality. Perturbed gut-microbiota (dysbiosis) and increased intestinal permeability (leaky-gut) with translocation of bacterial antigens, play critical role in obesity and metabolic syndrome, which are also major ACS risk factors. Additionally, Trimethylamine-N-Oxide (TMAO), a metabolite produced by phylum Proteobacteria in gut is implicated in developing ACS. As Proteobacteria is a major source of translocated antigen lipopolysaccharides (LPS), we hypothesized that ACS patients have leaky-gut condition characterized by dysbiosis with increased Proteobacteria, leading to elevated blood levels of TMAO and LPS. Methods: In a pilot case-control study, we enrolled 19 ACS patients (within 72-h of cardiac events) and 19 healthy-controls. Gut barrier function was determined using lactulose-to-mannitol urinary excretion ratio (L/M ratio). Stool microbiome composition was examined using16S sequencing and predictive functional analysis for LPS biosynthesis pathway by PICRUSt tool. Serum TMAO and LPS levels were measured. Results: ACS patients had increased Gammaproteobacteria compared to controls:1.8 ± 3.0 vs. 0.2 ± 0.4% (P = 0.04). Though Proteobacteria level was increased but not statistically significant: 4.1 ± 3.8 vs. 2.1 ± 1.7% (P = 0.056). L/M-ratio was three times higher in ACS patients; 0.06 ± 0.07 vs 0.023 ± 0.02, (P = 0.014). Surprisingly, there was no difference in the mean serum LPS or TMAO levels. However, PICRUSt analysis indicated increased Proteobacteria population increasingly contributed to LPS biosynthesis in ACS patients only. Conclusions: ACS patients likely to have leaky-gut and perturbed gut microbiota. Further studies are required to precisely define the role of dysbiosis in ACS.